Indonesia’s Maritime Vision and the Prospect of Cooperation in the South China Sea - Ramadhani, Masyithoh Annisa (Jurnal Hubungan Internasional, 2016)
The South China Sea has witnessed an array of global power projections given the huge amount of potential resources there. There are at least sixcountries who committed to be claimant states; China, Taiwan, Vietnam, Malaysia, Brunei, and the Philippines. Despite its role as the external actor, the United States claimed that their presence is needed in order to preserve stability in the region. This vexing situation has led to security dilemma which brings about power competition thereby maintaining peace and security would be critical. Therefore, Indonesia as one of region‘s rising powers who commits to be a non-claimant state, iterated the importance of establishing cooperation to preserve regional security under maritime vision albeit its national interests at stake there. This research examined the extent to which Indonesia maintains neutrality while pursuing national interests in the South China Sea under the maritime vision. Cooperation could therefore become the tools for (1) stabilising regional security given the increase of interdependence among states, (2) forging the immersion of regional unity, and (3) lessening the global power projections.